Synthesise and 2-Deoxyribose Degradation Inhibition of Two Benzalacetone Derivatives - Handayani, Sri; Matsjeh, Sabirin; Anwar, Chairil; Atun, Sri (2010)
Two benzalacetones deivatives - Le. 3-hydroxyben/alacetone and 4-hydroxy-3-methoxybenzalacetone -have been synthesized and its antioxidant activity have also been tested. Synthesize were done through cross aldol condensation reaction under basic condition using ethanol as solvent. Re-crystailization using methanol was used to obtain pure material, which were yielding 50.62% of 3-hydroxybenzalacetone and 52.38% of 4-hydroxy-3-methoxvbenzalacetone. Resulting materials have been characterized by TLC, H1K, and NMR spectrometer. The activity tested performed with Deoxyibose assay. 3-hydroxibenzalacetone has higher antioxidant activity than 4-hydroxy-3-methoxybenzalacetone, which 3-hydroxybcnzalacetone more active inhibited 2-Deoxyribose degradation than 4-hydroxy-3-methoxybenzalacetone